2019
DOI: 10.1080/10412905.2019.1580225
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal activity of cashew nut shell liquid associated with essential oils from Cordia verbenacea and Psidium guajava on Rhipicephalus microplus

Abstract: The aim of this study was to assess the effectiveness of cashew nut shell liquid (CNSL), Cordia verbenacea and Psidium guajava, both alone and in association against Rhipicephalus microplus. Larval packet and adult immersion tests were conducted in concentrations ranging from 3.1 at 100.0mg mL −1. CNSL was effective against engorged females (99.6%) at 100.0mg mL −1 and against larvae (99.2 %) at 50.0mg mL −1. The highest efficacy on engorged females was achieved by the essential oils of P. guajava at 12.5mg mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Nepal [14] Leave (E)-nerolidol (E)-caryophyllene Egypt [15] Leave Limonène Hydrocarbons Monoterpenes Oxygenated Monoterpenes Parkistan [26] Leave α-phellandrene eucalyptol α-terpineol spathulenol caryophyllene dihydrocarveol acetate nerolidol caryophyllene oxide oxygenated monoterpene sesquiterpene hydrocarbons oxygenated sesquiterpene monoterpene hydrocarbons the majority compounds depend on the variety of the tree Oman [27] Leave iso-caryophyllene veridiflorence farnesene Pakistan [16] Leave β-caryophyllene Sesquiterpene hydrocarbon Nakhon [28] Leave Limonene α-Pinene Alexandria [29] Leave α-pinene (E)-caryophyllene (E)-nerolidol FazendaTabuleiros II [30] Leave β-caryophyllene India [31] Leave α-terpinyl acetate trans-caryophyllene nerolidol Brazil [32] Leave α -Humulene β-caryophyllene β -Selinene α -Selinen…”
Section: Monoterpene Hydrocarbonsmentioning
confidence: 99%
“…Nepal [14] Leave (E)-nerolidol (E)-caryophyllene Egypt [15] Leave Limonène Hydrocarbons Monoterpenes Oxygenated Monoterpenes Parkistan [26] Leave α-phellandrene eucalyptol α-terpineol spathulenol caryophyllene dihydrocarveol acetate nerolidol caryophyllene oxide oxygenated monoterpene sesquiterpene hydrocarbons oxygenated sesquiterpene monoterpene hydrocarbons the majority compounds depend on the variety of the tree Oman [27] Leave iso-caryophyllene veridiflorence farnesene Pakistan [16] Leave β-caryophyllene Sesquiterpene hydrocarbon Nakhon [28] Leave Limonene α-Pinene Alexandria [29] Leave α-pinene (E)-caryophyllene (E)-nerolidol FazendaTabuleiros II [30] Leave β-caryophyllene India [31] Leave α-terpinyl acetate trans-caryophyllene nerolidol Brazil [32] Leave α -Humulene β-caryophyllene β -Selinene α -Selinen…”
Section: Monoterpene Hydrocarbonsmentioning
confidence: 99%
“…Plant mixtures have been shown to have synergistic effects on numerous species, such as bacteria ( Didry et al ., 1994 ), fungus ( Mugnaini et al ., 2012 ), gastro-intestinal parasites ( Ntalli et al ., 2011 ), and insects ( Ntalli et al ., 2011 ). Furthermore, the associations are viable for controlling bovine ticks ( Vinturelle et al ., 2017 ; De Carvalho Castro et al ., 2019 ; Shezryna et al ., 2020 ). Overall, researchers found that mixing volatile oils showed good action on R .…”
Section: Discussionmentioning
confidence: 99%
“…Sesquiterpene potential has also been reported, such as the β-caryophyllene showing contact and fumigant activity against adults of Megoura japonica Matsumura (Hemiptera: Aphididae) recorded an LC 50 of 0.072 µg/L and 8.82 mg/L [90]; likewise, De-Carvalho et al [91] mentioned that β-caryophyllene and gurjinene founded in Cordia verbenacea DC. (Lamiales: Boraginaceae) have an acaricidal effect against R. microplus, another compound identified in our study.…”
Section: Discussionmentioning
confidence: 99%